Inovasi Biopori Berbasis Teknologi Tepat Guna untuk Peningkatan Kualitas Air dan Sanitasi di Kalangbangi Lor A - Trikorianto, Miftah Aji; Ramadhani, Shafira Catur Yanda; Dayati, Dewi; Permata, Leni Cahaya; Parasmita, Puput Sylva; Prasetyo, Rafly Ferry; Rafi, Muhammad; Aulia, Ferinda; Nayotama, Jati Abrar; Saputra, Zevvan Aldias; Sutoyo , Sutoyo (Universitas Muhammadiyah Yogyakarta, 2025)
More sustainable public health and environment require a holistic and synergistic approach. Community service activities as an effort to transfer knowledge are considered appropriate to build synergy in improving public health and the environment. Located in Kalangbangi Lor A Hamlet, Ngeposari Village, Gunungkidul, through situational analysis, it was found that 65% of the area experienced waterlogging during the rainy season, 50% of people reported difficulty in accessing clean water during the dry season, and 45% of household organic waste was still simply thrown away or burned. The lack of awareness of the importance of environmental health certainly requires an active role from various parties, including related agencies and the general public. The purpose of this community service program is to integrate biopore technology and environmental health to provide a comprehensive solution to the challenges faced by the community in overcoming the problem of waterlogging and waste. The methods used in this community service are socialization and training. The results of the community service program show that biopores have succeeded in increasing public knowledge, with understanding increasing from 15% to 50%, and 60% of participants are able to make biopores independently. A total of 24 biopore holes were successfully implemented in three RTs, with 50% of families starting to sort organic waste, producing around 5 kg of quality compost in one month for agriculture and greening. The positive impact on the environment can be seen from the reduction in waterlogging by 25%, to 40%, and 80% of respondents felt a decrease in waterlogging and a 70% reduction in organic waste. With the sustainability of this program, it is expected to provide greater benefits to the community and create a healthier and more productive environment